Intrinsic and internalized modes of teaching motivation. Issue 1 (13th May 2014) - Wilkesmann, Uwe; J. Schmid, Christian
Abstract : Purpose: – The introduction of New Public Management in the German system of higher education raises issues of the academics' motivation to do research and to teach. The purpose of this paper is to present evidence-based findings about contextual factors which influence intrinsic and related modes of internalized teaching motivation in German higher education institutions. The paper discusses parallels between internalized forms of motivation and public service motivation (PSM). In accordance with self-determination theory (SDT), the paper empirically tests factors which correlate with autonomous motivation to teach. The paper also addresses the issue of the crowding effect of intrinsic motivation by selective incentives. Design/methodology/approach: – The analyses are based on the data of two online surveys among German professors ( n =2, 061) representative for the population of state-governed universities. To test the theory-driven hypotheses the paper used multivariate regression analysis. Findings: – The results support the basic claims of the SDT that intrinsic teaching motivation is facilitated by social relatedness, competence, and partly by autonomy for German professors, too. If teaching is managed by objective agreements intrinsic motivation is significantly decreased. Originality/value: – The authors translated, reformulated, and applied the SDT framework to academic teaching. The analysis presents evidence that the management of autonomy-supportive work environmental factors is also superior to selective incentives in higher education institutions. The study on academic teaching motivation is a specific contribution to PSM research. Academic teaching in public higher education institutions is a service to the public.